DAMPAK KONVERSI LAHAN SAWAH DI KAWASAN USAHA AGRIBISNIS TERPADU (KUAT) GALING KOMPLEK TERHADAP PRODUKSI BERAS - SUSILAWATI, SUSILAWATI; MULYATI, SRI; MUSLIMAH, MUSLIMAH (Jurnal Social Economic of Agriculture, 2016)
Increased food continues to be done annually. Rice is the staple food in Indonesia and also consumed by people outside Indonesia. Rice production is the enhanced production of rice paddy fields. Therefore, increased food security will support national development goals. One of the activities that support food security is by controlling wetland conversion. This study aims to determine what factors are causing the wetland conversion to non-agricultural use and how the impact of wetland conversion to rice production which is an element of food security. The method used in this research is descriptive qualitative method, the location is determined intentionally (purposive) that Galing Integrated Agribusiness Complex Area, Galing Sub-District, Sambas District. Galing is one of Integrated Agribusiness Complex Area with rice as main commodity. The population in this study are all rice farmers (crop) in Integrated Agribusiness Galing Complex. While the sample total of 42 rice farmers. Factors that cause wetland conversion to non-agricultural use are price, survival of the plant, and cultural factors. While the impact of wetland conversion to rice production which is an element of food security are: 1) the reduction in the production of food crops, particularly rice, 2) reduction in paddy fields, and 3) reduced labor in agriculture, especially food crops.